2018
DOI: 10.1007/s12289-018-1434-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of forming parameters in incremental sheet forming using a micromechanics based damage model

Abstract: The incremental sheet forming (ISF) process is considered as a feasible solution for forming a variety of small batch and even customised sheet components. The quality of an ISF product is affected by various process parameters, e.g. sheet material, stepdown, feed rate, tool diameter and lubricant. To produce an ISF part of sufficient quality and accuracy without defects, optimal parameters of the ISF process should be selected. In the present work, experiments and FE analyses were conducted to evaluate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…To the authors' knowledge, such an experimental process has not been tested or described in the literature. In fact, in the scope of the present project, forming depth was considered an indicator of formability: forming depth is deemed as an indicator of the formability of formed parts, as described in [39][40][41][42][43][44][45][46]. Furthermore, as an aim and novelty in the scope of this paper, a prediction equation for both accuracy and formability based on weights and biases was derived, as well as the joint partitioning weight of the neural network was adopted to assess the Relative Importance (RI) of SPIF parameters on the output.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, such an experimental process has not been tested or described in the literature. In fact, in the scope of the present project, forming depth was considered an indicator of formability: forming depth is deemed as an indicator of the formability of formed parts, as described in [39][40][41][42][43][44][45][46]. Furthermore, as an aim and novelty in the scope of this paper, a prediction equation for both accuracy and formability based on weights and biases was derived, as well as the joint partitioning weight of the neural network was adopted to assess the Relative Importance (RI) of SPIF parameters on the output.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that due to the better ductility titanium grade 2 sheets exhibited better forming and fracture limits compare to the grade 4 sheets. Gatea et al 14 carried out the experimental and FE analysis for ISF process to evaluate the impact of step down, feed rate and tool diameter on formability of titanium grade and grade 2 using GTN damage model. Daleffe et al 15 have analysed ISF of CP-Ti Grade-2 at room temperature and showed that the limit wall angle for the CP-Ti grade 2 sheet of 0.5 mm thickness is 47°.…”
Section: Introductionmentioning
confidence: 99%
“…Formability is estimated as a function of petal height [12] which is an indirect measurement method in production technology. By using micrometer petal height is measured for every experimental run as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%